Pemanfaatan Lahan Waduk Pusong oleh Masyarakat untuk Tempat Usaha Menurut Konsep Milk Al-Daulah dan UU No. 17 Tahun 2019 tentang Sumber Daya Air : Penelitian di Waduk Pusong Kecamatan Banda Sakti Kota Lhokseumawe (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2025)
This study aims to examine the illegal land ownership of the Pusong Reservoir in Banda Sakti Subdistrict, Lhokseumawe City by the local community, viewed from the perspective of Islamic law, specifically the concept of milk al-daulah, and national legislation, particularly Law No. 17 of 2019 on Water Resources. The phenomenon of land ownership in the reservoir has resulted in various impacts, including ecosystem damage and the potential for conflicts between the community and the government. This research uses a juridical-sociological approach with a descriptive-analytical qualitative method. Data were collected through interviews, observations, and literature studies. The findings show that the community’s ownership of the reservoir land, which is used for business and residential purposes, is in conflict with the principle of milk al-daulah and Law No. 17 of 2019, which stipulates that water resources are controlled by the state and must be used for public interest. The weak implementation of government oversight in managing this land has led to an imbalance between the interests of the community and the state. This study recommends better management of the reservoir land to ensure ecosystem sustainability and community welfare.